2015
DOI: 10.1007/s12011-015-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of Trace Elements in Liver Cirrhosis Patients and Their Role in Prognosis of Disease

Abstract: The objectives of this study are to evaluate trace elements in patients with liver cirrhosis and to assess their association with severity of the disease. One hundred fifty cirrhotic subjects of either sex ranging in age from 20-70 years were included in the study, and the results were compared with 50 age- and sex-matched healthy control subjects. All cirrhotic subjects were assessed for severity of disease as mild (Child A), moderate (Child B), and severe (Child C) as per Child-Pugh classification. Routine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 22 publications
6
49
1
1
Order By: Relevance
“…Our results indicate a selenium deficiency in patients with liver cirrhosis and are consistent with previously published study findings. Nangliya et al showed the relationship between the severity of liver cirrhosis and reduced concentration of selenium [10]. Kazi et al noticed that the concentrations of selenium and zinc were reduced in patients with cirrhosis and liver cancer and negatively correlated with the concentrations of heavy metals (cadmium and arsenic) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate a selenium deficiency in patients with liver cirrhosis and are consistent with previously published study findings. Nangliya et al showed the relationship between the severity of liver cirrhosis and reduced concentration of selenium [10]. Kazi et al noticed that the concentrations of selenium and zinc were reduced in patients with cirrhosis and liver cancer and negatively correlated with the concentrations of heavy metals (cadmium and arsenic) [11].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, information from case–control studies indicates higher circulating copper and lower zinc levels in patients with hepatitis C (Ko et al , 2005) and liver cirrhosis (Rahelic et al , 2006; Nangliya et al , 2015). Additional evidence suggests a link between hepatitis C infection and higher antioxidant enzyme Cu/Zn-SOD activity which has also been observed to be high in liver biopsies of NAFLD patients (Ko et al , 2005; Perlemuter et al , 2005).…”
mentioning
confidence: 99%
“…During the first 48 h of the experiment, no alterations were observed, but after 72 and 96 h, a slight decrease vs. control was obtained [10]. No influence of any treatment used in our experiment on the liver Mg is also very substantial as the proper functioning of this detoxifying organ is an issue of great importance, particularly that psychiatric subjects must undergo a long-term therapy [2] and some connections among magnesium, selenium and disturbances of the liver have already been reported [32, 33]. …”
Section: Discussionmentioning
confidence: 76%